The design of an online directory of expertise for Islamic and Arabic studies in Malaysia - Sahrir, Muhammad Sabri; Ismail, Taufik; Chik, Abdul Rahman (2015)
The offered programmes for Islamic and Arabic studies at higher learning institutions in Malaysia have proven that the efforts towards the empowerment of this field are currently ongoing process and shown a positive transformation. Furthermore, the number of experts and practitioners who are actively involved in the field of Islamic and Arabic studies is great indeed. In order to ensure that these areas are always relevant and continuously to be strengthened, an expertise directory is created involving experts in the field of Islamic and Arabic studies. This research aims to gather suggestions and feedback from respondents on the design and development of an expertise directory in Islamic and Arabic studies in Malaysia by using ADDIE instructional design model. This research is a mix of quantitative and qualitative methodologies that involved 31 experts from educational institutions from the field of Islamic and Arabic studies. The questionnaires were distributed to the respondents by email and online Google survey. Based on the findings, the average respondent expressed their positive feedback on the expertise directory and provide further suggestions and comments to improve the directory. It is an important an academic reference and one stop center for the Islamic and Arabic Studies in Malaysia. It has several characteristics which consist of important information for the academicians and experts in the field. This directory has the potential of future enhancement of design and commercialization by the higher level public higher education authority in Malaysia.